Heavy metal contamination (zinc, copper, lead, cadmium) in shrimp and cockles at Sungai Haji Dorani, Sabak Bernam, Selangor - Mohd Zamri, Fatin; Musa, Farah Adilah (2020)
Heavy metal pollution in rivers gives threat to public water supplies and also to the consumer of fishery sources. Heavy metals constitute a core group of aquatic pollutants via its bioaccumulative and non-biodegradable properties in food. Human may be contaminated by organic and inorganic pollutants associated with aquatic systems by consumption of contaminated fish and other aquatic foods from this environment. Heavy metals, such as cadmium (Cd), lead (Pb), and zinc (Zn), as well as metallic like copper (Cu) from natural and anthropogenic sources continuously enter the marine environment. Subsurface migration, fertilizer runoff from farms, storm water from streets, and other forms of diffuse pollution are now recognized as having serious environmental consequences. In more than 50 percent of estimated cases in which water quality goals are not achieved, diffuse pollution is cited as the main cause (International Institute for Applied Systems Analysis (IIASA)).